IMPLEMENTASI PROGRAM REHABILITASI HUTAN DAN LAHAN MELALUI KEGIATAN HUTAN RAKYAT DI DESA KALISIDI KECAMATAN UNGARAN BARAT KABUPATEN SEMARANG - Dinda Gitahapsari; Amni Zarkasyi Rahman (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2016)
The resources of forest and land provide so many advantages for human life. One of the challenges and problems that still be faced in this time is the land degradation that can cause a variety of affects and impact on the environment and human life. The government imposed a forest and land rehabilitation program as an effort to improve and restore the functionality and productivity of land that suffered damage. The aims of this study are to describe the implementation of forest and land rehabilitation programs through the activities of community forest in Kalisidi Village Ungaran Barat Sub-District, Semarang Regency. Besides, to figure the factors that supporting and inhibiting implementation of the program. This study used descriptive qualitative approach. The data in this study were obtained from interviews with informants, observation, and documents. This study used a case study approach. The results of this study has shown that the implementation has been carried out in accordance with the applicable regulations, Permenhut-II Number: P.70/Menhut-II/2008 about Technical Guidelines for Forest and Land Rehabilitation. Activities that have been conducting is preparation, cultivation and conservancy of plants. That is indicated by the formation of ten farmer groups in Kalisidi Village that uses Agroforestry system, yet it still has deficiencies. Based on the implementation model of Van Meter and Van Horn, the supporting factors are policy standards and objectives, inter-organizational communication, the characteristics of the implementing agencies, the disposition of implementers and the economic environment. While the inhibiting factors are policy resources, the social and political environment. Advice that can be given are strengthening the institutional against farmer groups, increasing quantity of the forestry field extension agent, the need for a Regional Regulation concerning the management of community forest in Semarang Regency, increasing surveillance against the existence of the wood collectors and reviewing the rules of administration of the products that derived from community forest.